Non-invasive tunnelled catheter reposition (NTCR): A simple and safe method to restore central tunnelled catheter function for haemodialysis - Porazko, Tomasz (Sci Rep, 2020)
Despite all efforts, still many end-stage kidney disease (ESKD) patients are dialysed using a central tunnelled catheter (CTC) as vascular access. When the CTC blood flow becomes ineffective, a number of protocols are advised. However, all of them are time- and cost-consuming. The manoeuvre of a non-invasive tunnelled catheter reposition (NTCR) was introduced to restore the CTC function. NTCR was based on gentle movements of the CTC, with or without a simultaneous flushing of the CTC lines, which resulted in a quick reposition of the CTC tip. This study comprises the analysis of a total of 297 NTCRs, which were performed in 114 patients, thus enabling an effective blood flow after 133 procedures (44.7%).Partially effective blood flow followed 123 procedures (41.4%), and it failed altogether in 41 cases (13.9%). Overall, 86% of conducted NTCRs improved the CTC patency to perform a haemodialysis session. The procedure could be successfully repeated, with a similar result after the first and the second attempt. Complications were observed only after 3.4% of all interventions. The novel NTCR manoeuvre was safe and effective in the majority of the CTC dysfunction episodes. It seemed to reduce fibrinolytic usage, allowed an immediate haemodialysis session commencement, therefore, it might save both the costs and the nursing staff time.